Exploring the Role of Destination Resilience Plans in Promoting Tourism: A Literature Review - Caluza, Cristina (JPAIR Multidisciplinary Research, 2024)
The study investigates the critical importance of destination resilience in enhancing tourism, particularly in the wake of challenges such as the COVID-19 pandemic. The primary aim of the research is to analyze how effective governance, stakeholder engagement, resource management, and risk assessment contribute to the resilience of tourist destinations and micro, small, and medium enterprises (MSMEs). To achieve this, the study employs a comprehensive literature review methodology, synthesizing existing research on destination resilience strategies and their implications for tourism promotion. The findings reveal that destination resilience plans significantly impact tourism performance, stakeholder participation, and sustainable development. Additionally, the study highlights the necessity of integrating innovative practices and technology to bolster the resilience of tourism sectors. In conclusion, this research provides valuable insights for destination management organizations, policymakers, and industry researchers, emphasizing the need for strategic planning and collaboration to foster long-term sustainability and resilience in tourism. The study serves as a foundation for future investigations and policy-making in the realm of sustainable tourism, addressing existing gaps in the literature and offering practical recommendations for enhancing destination resilience.
Keywords: Destination resilience; Tourism promotion; Crisis communication; Entrepreneurship characteristics; Marketing strategy; Sustainable production performance; Micro, Small, and Medium Enterprises (MSMEs; COVID-19; Community resilience; Smart governance; Risk management; Philippines